Living the gospel of Jesus Christ : Orthodox and Evangelical approaches to discipleship and Christian formation - Oxbrow, Mark (Anglican priest); Grass, Tim (Regnum Books International, 2021)
Living the Gospel of Jesus Christ addresses the challenge of whole-life discipleship and Christian formation for the contemporary church. Authors from around the world bring together insights from their Evangelical and Orthodox traditions to enrich the journey of witness and martyrdom, a faithful daily living of the Christian gospel which speaks with integrity to a world seeking truth.
Keywords: Christian life -- Orthodox Eastern authors.; Christian life -- Evangelical authors.; Discipling (Christianity); Spiritual formation -- Christianity.; Formation de disciples (Religion); Christian life; Evangelicalism